Pregnancy Outcome in Women with Decreased Fetal Movement Beyond 34 Weeks of Gestation - Sharma, Poonam; Ghimire, Asmita (Journal of Institute of Medicine Nepal, 2022)
Introduction The fetal movement though subjective still is considered an important sign of fetal well-being. It is used as the first method for fetal well being assessment. Decreased fetal movement(DFM) always alerts the obstetricians and needs appropriate intervention as it is generally found to be associated with poor fetomaternal outcome. This study was conducted to determine the pregnancy outcome in women with decreased fetal movements at gestational age ≥34 weeks to 42 weeks of gestation. Methods This was a hospital- based retrospective observational study done in Obstetrics and Gynaecology department of Tribhuvan University Teaching Hospital Nepal from April 2020 to April 2021. Descriptive analysis and data processing was done by using IBM SPSS Statistics 22. Results There were a total of 82 women with decreased fetal movement. Among all of these women induction of labor was done in 35.5% while - 23.1% had a preterm delivery, 47.56% had a cesarean delivery and 51.1% had a vaginal delivery with 1.2% -vacuum delivery. Though there were higher rates of low APGAR score (15.8%), Meconium stained liquor (MSL) (21.9%) and Neonatal Unit admission (NNU) (21.9%), all the babies admitted were discharged except for one perinatal death (1.2%). There was no still birth. Conclusion Although Perinatal mortality was low in women with decreased fetal movement with negligible still birth, however, there were increased MSL and neonatal admission. Hence raising awareness of DFM among women , its early identification , further assessment with ultrasound, cardiotocogram and structured management protocol is beneficial .